Absolute risk of venous and arterial thromboembolism in thrombophilic families is not increased by high thrombin-activatable fibrinolysis inhibitor (TAFI) levels - Folkeringa, Nienke; Coppens, Michiel; veeger, Nic J. G. M.; Bom, Victor J. J.; Middeldorp, Saskia; Hamulyak, Karly; Prins, Martin H.; Büller, Harry R.; van der Meer, Jan (Thrombosis and Haemostasis, 2008)
High levels of thrombin-activatable fibrinolysis inhibitor (TAFI) are a supposed risk factor for thrombosis. However, results from previous studies are conflicting. We assessed the absolute risk of venous and arterial thromboembolism in subjects with high TAFI levels (>126 U/dl) versus subjects with normal levels, and the contribution of other concomitant thrombophilic defects. Relatives from four identical cohort studies in families with either deficiencies of antithrombin, protein C or protein S, prothrombin 20210A, high factor VIII levels, or hyperhomocysteinemia were pooled. Probands were excluded. Of 1,940 relatives, 187 had high TAFI levels. Annual incidences of venous thromboembolism were 0.23% in relatives with high TAFI levels versus 0.26% in relatives with normal TAFI levels (adjusted relative risk [RR] 0.8; 95% confidence interval [CI], 0.5–1.3). For arterial thrombosis these were 0.31% versus 0.23% (adjusted RR 1.4; 95% CI, 0.9–2.2). High levels of factor VIII, IX and XI were observed more frequently in relatives with high TAFI levels. Only high factor VIII levels were associated with an increased risk of venous and arterial thrombosis, independently of TAFI levels. None of these concomitant defects showed interaction with high TAFI levels. High TAFI levels were not associated with an increased risk of venous and arterial thromboembolism in thrombophilic families.
Keywords: Arterial thromboembolism; TAFI; venous thromboembolism